People with HIV have a higher risk of COVID‐19 diagnosis but similar outcomes to the general population. Issue 10 (8th April 2022) - Tang, Michael E.; Gaufin, Thaidra; Anson, Ryan; Zhu, Wenhong; Mathews, William C.; Cachay, Edward R.
Abstract: Background: We investigated the effect of HIV on COVID‐19 outcomes with attention to selection bias due to differential testing and comorbidity burden. Methods: This was a retrospective cohort analysis using four hierarchical outcomes: positive SARS‐CoV‐2 test, COVID‐19 hospitalization, intensive care unit (ICU) admission and hospital mortality. The effect of HIV status was assessed using traditional covariate‐adjusted, inverse probability‐weighted (IPW) analysis based on covariate distributions for testing bias (testing IPWs), HIV infection status (HIV‐IPWs) and combined models. Among people living with HIV (PWH), we evaluated whether CD4 count and HIV plasma viral load (pVL) discriminated between those who did and those who did not develop study outcomes using receiver operating characteristic analysis. Results: Between March and November 2020, 63 319 people were receiving primary care services at the University of California San Diego (UCSD), of whom 4017 were PWH. The PWH had 2.1 times the odds of a positive SARS‐CoV‐2 test compared with those without HIV after weighting for potential testing bias, comorbidity burden and HIV‐IPW [95% confidence interval (CI): 1.6–2.8]. Relative to people without HIV, PWH did not have an increased rate of COVID‐19 hospitalization after controlling for comorbidities and testing bias [adjusted incidence rate ratio (aIRR) = 0.5, 95% CI: 0.1–1.4]. PWH did not have a different rate of ICU admission (aIRR = 1.08, 95% CI: 0.31–3.80) or of in‐hospital death (aIRR = 0.92, 95% CI: 0.08–10.94) in any examined model. Neither CD4 count nor pVL predicted any of the hierarchical outcomes among PWH. Conclusions: People living with HIV have a higher risk of COVID‐19 diagnosis than those without HIV but the outcomes are similar in both groups.